Analisis Framing Pemberitaan Pemindahan Ibukota Negara (IKN) Indonesia Di Media Online Republika.co.id dan Tempo.co - Hutapea, Edison Bonartua; Sinambela, Lasria (FISIP Universitas Bung Karno, 2023)
AbstractMedia has an important role on giving information relating to the government policy in moving the national capital of Indonesia to East Kalimantan and inaugurating the zero point of this national capital. The news conveyed by the media about the relocation of national capital actually functions as information and education. After the news of relocating the national capital has spreaded, the online media started to review this information. How does media study this information? To answer this question, researcher has conducted study to examine the news by framing the news about moving the national capital of Indonesia to East Kalimantan and inaugurating the zero point of this national capital from media online Republika.co.id and Tempo.co. The purpose of this research is to find out the difference in framing the social reality construction, commodification of content and ideology of the Republika.co.id and Tempo.co. This study uses a qualitative method with Pan and Kosick model framing analysis. The result of this study based on syntatic, script, thematic, and rhetorical devices find that there are differences in media framing by Republika.co.id and Tempo.co in constructing news. Republika.co.id focuses on highlighting and supporting the government’s policy of transfering the IKN, while Tempo.co emphasize criticism for government. Keywords: Framing, Moving the National Capital of Indonesia, Zero Point Inauguraton, Online Media, Qualitative